Japanese structure survey of radiation oncology in 2010. (21st August 2018) - Numasaki, Hodaka; Teshima, Teruki; Nishimura, Tetsuo; Akuta, Keizo; Ando, Yutaka; Ikeda, Hiroshi; Kamikonya, Norihiko; Koizumi, Masahiko; Sasaki, Tomonari; Sekiguchi, Kenji; Tago, Masao; Terahara, Atsuro; et al.
Abstract: We evaluated the evolving structure of radiation oncology in Japan in terms of equipment, personnel, patient load, and geographic distribution to identify and overcome any existing limitations. From March 2011 to June 2013, the Japanese Society for Radiation Oncology conducted a questionnaire based on the Japanese national structure survey of radiation oncology in 2010. Data were analyzed based on the institutional stratification by the annual number of new patients treated with radiotherapy per institution. The estimated annual numbers of new and total (new plus repeat) patients treated with radiation were 211 000 and 251 000, respectively. Additionally, the estimated cancer incidence was 805 236 cases, with 26.2% of all newly diagnosed patients being treated with radiation. The types and numbers of treatment devices actually used included linear accelerator (LINAC; n = 829), telecobalt ( n = 9), Gamma Knife ( n = 46), 60 Co remote afterloading system (RALS; n = 28), and 192 Ir RALS ( n = 131). The LINAC system used dual-energy functions in 586 units, three-dimensional conformal radiotherapy functions in 663, and intensity-modulated radiotherapy (IMRT) functions in 337. There were 564 JASTRO-certified radiation oncologists, 959.2 full-time equivalent (FTE) radiation oncologists, 1841.3 FTE radiotherapy technologists, 131.3 FTE medical physicists, 121.5 FTE radiotherapy quality managers, and 649.6 FTE nurses. The frequency of IMRT use significantly increased during this year. To conclude, although there was a shortage of personnel in 2010, the Japanese structure of radiation oncology has clearly improved in terms of equipment and utility.